Physiological and technical aspects of ''6-a-side'' soccer drills - Tessitore, A.; Meeusen, R.; Piacentini, M. F.; Demarie, S.; Capranica, L. (The Journal of Sports Medicine and Physical Fitness, 2006)
Aim: The purposes of the present study were: 1) to evaluate heart rate and technical-tactical differences, if any, during ''6-a-side'' drills, played on 2 pitch dimensions (30¥40 m and 50¥40 m) and duration (3 min and 8 min); 2) to assess the variability of data between repeated experimental sessions; 3) to evaluate training intensities from heart rate at lactate threshold. Methods: Laboratory measurements of maximal oxygen consumptions, maximum heart rates and lactate thresholds were performed on 9 soccer players who played at Regional level. For test and retest field sessions, the exercise intensities were calculated from heart rate monitoring and match analysis (number of actions, consecutive passes, players involved in a single action) was performed. Results: No significant differences were found in heart rate frequency distributions between test and retest sessions. Statistically significant differences in frequency distributions of heart rate were found only between the 3 min and 8 min drills played on the 40¥50 m pitch. Regarding exercise intensity, significant differences (P<0.01) were found for pitch dimension, with higher intensities shown during the 30¥40 m pitch trials. When technical data were related to time units, no differences were found among experimental settings. Conclusion: These data indicate that coaches could better modulate the training intensity by varying the pitch dimension, with the smaller individual playing area (30¥40 m) having a large impact on the metabolic demands of exercise.